Non-reciprocal phase transitions - Fruchart, Michel; Hanai, Ryo; Littlewood, Peter B.; Vitelli, Vincenzo (Nature (London), 2021)
Out of equilibrium, a lack of reciprocity is the rule rather than the exception. Non-reciprocity occurs, for instance, in active matter 1 – 6 , non-equilibrium systems 7 – 9 , networks of neurons 10 , 11 , social groups with conformist and contrarian members 12 , directional interface growth phenomena 13 – 15 and metamaterials 16 – 20 . Although wave propagation in non-reciprocal media has recently been closely studied 1 , 16 – 20 , less is known about the consequences of non-reciprocity on the collective behaviour of many-body systems. Here we show that non-reciprocity leads to time-dependent phases in which spontaneously broken continuous symmetries are dynamically restored. We illustrate this mechanism with simple robotic demonstrations. The resulting phase transitions are controlled by spectral singularities called exceptional points 21 . We describe the emergence of these phases using insights from bifurcation theory 22 , 23 and non-Hermitian quantum mechanics 24 , 25 . Our approach captures non-reciprocal generalizations of three archetypal classes of self-organization out of equilibrium: synchronization, flocking and pattern formation. Collective phenomena in these systems range from active time-(quasi)crystals to exceptional-point-enforced pattern formation and hysteresis. Our work lays the foundation for a general theory of critical phenomena in systems whose dynamics is not governed by an optimization principle. A theoretical study of non-reciprocity in collective phenomena reveals the emergence of time-dependent phases heralded by exceptional points in contexts ranging from synchronization and flocking to pattern formation.